Cone Calorimetry Studies of Benzoxazine-Epoxy Systems Flame Retarded By Chemically Bonded Phosphorus or Silicon - Spontón, Marisa Elisabet (2009)
The combustion behaviour of phosphorus- and silicon-containing benzoxazine-epoxy systems has been studied by LOI and cone calorimetry giving a clear evidence that incorporation of 3.5% P into the benzoxazine-epoxy systems, resulted in flame retardation while the silicon-containing copolymer was found to have no improvement in the LOI and cone calorimeter data, with values similar to the polymers without heteroatom, thus indicating that the 3.9% silicon content has no flame retarding effect. The peak of heat release rate value is reduced significantly for the phosphorus-containing benzoxazine as a result a combination of condensed-phase and gas-phase mechanisms.The incorporation of phosphorus or silicon into the modified benzoxazine-epoxy system increases the smoke hazard and the CO emissions compared to the heteroatom-free system.